'Folds of the heart': performing life experience, emotion and empathy in Japanese tango music culture. Issue 1 (2nd January 2019) - Asaba, Yuiko
ABSTRACT: In the Argentine tango music culture of Japan, to have undergone many life experiences is considered critical in order to perform the powerful emotions of tango. Narratives by Japanese tango musicians stress 'each musician's feelings' as crucial in shaping a good tango performance, while empathy is considered important in cultivating such feelings. Based on the author's field research in Japan and Argentina, and by adding a different nuance to Carolyn Pedwell's notions of transnational 'affective relations', this essay examines how Japanese historical narratives, rooted in aesthetic and moral ethos, fabricate discourses of tango authenticity by Japanese musicians. Taking a closer look at the ways in which Japanese musicians discuss tango's emotion illuminates how Argentine tango's aesthetics of emotion are given renewed meanings through the channelling of cultural and historical symbols in Japanese contexts. This article argues that Japanese tango musicians create their discourses surrounding tango authenticity at such transnational instances when aesthetics, affect and morality intersect.